(untitled) (Journal of Philosophy Culture and Political Science, 2018)
Today in spite the fact that it is taking place numerous tumults, Kazakhstan could introduce itself as a country of peace and stability. However, in fact we see that we should consider this question from new approach. Unfortunately a few extremist occasions occurred recently make us to research this phenomenon thoroughly. Terms extremism, terrorism become one of the most well-known. It became a tool of realization of definite aims of different religious, political, national movements. Especially, maligning Islam as extremism is happening very often. If initially extremist phenomena had local feature, now it turned into global issue. In the context of the process of globalization, regional safety turned into global safety. Keywords: world, religion, stability, extremism, terrorism, and security.